OPTIMASI KONDISI REAKSI HIDROGENASI METIL ESTER DALAM PENINGKATAN AKTIVITAS SURFAKTAN BERBASIS MINYAK JELANTAH - Siaka, I Made; Hermanto, Yuky Astary; Widihati, Ida Ayu Gede (Jurnal Kimia (Journal of Chemistry); Vol. 6, No. 2 Juli 2012)
This paper discusses the optimization of reaction condition of methyl ester hydrogenation in the process of making surfactant from used cooking oil. The synthesis of surfactant involved the esterification reaction of used cooking oil, base-catalyzed transesterification, and hydrogenation reaction of methyl ester (methyl laurate), followed by the sulfatation using sulfuric acid and neutralization using sodium hydroxide. The hydrogenation reaction was performed in the presence of Zn, as the catalyst, at various temperatures (200oC, 220oC, and 240oC) and reaction times (1, 1½, and 2 hours). The surfactant activities testing was conducted through surface tension measurement using the drop weight method and emulsion stability duration testing to find out the optimum condition of each variable. The result indicated that the temperature of the hydrogenation reaction had no effect to the activities of surfactant produced, but the time reaction had. The surfactant activities testing showed that the reaction time of the hydrogenation reaction needed to give the smallest surface tension of water (32 dyne/cm average) was 1½ to 2 hours. More over, the reaction times ware also able to give the longest emulsion stability of 450.6 seconds for cooking oil-water emulsion and 454.6 seconds for used cooking oil-water emulsion. Therefore, the reaction times of 1½-2 hours  could be categorized as the optimum reaction time.
Keywords: surfactant, used cooking oil, hydrogenation, methyl ester